Analysis of the Attraction of Using e-Money among Indonesian Millennials - Wisnu Yuwono; Johny Budiman; Hendriyanto Hendriyanto; Dessy Alliandrina (Cita Konsultindo Research Center, 2024)
The percentage of e-money users in Indonesia is still low, not comparable to several neighboring countries. Even though the Indonesian government has made regulations regarding e-money security, in terms of digital payments it is still low. This research analyzes the determining factors for the use of e-money for millennials. This research was conducted in Batam City, which is considered representative of Indonesia. The sample size was 400 millennial respondents, using SPSS version 29.0, it was concluded that perceived usefulness, performance expectancy, social influence and trust had a significant positive effect on intention to use e-money. Meanwhile, perceived use and effort expectancy do not have a significant effect. This condition actually indicates that the existence of government regulations regarding payment security has the most significant impact in encouraging the use of e-money.